The management of type 1 diabetes in Australian primary schools. (September 2014) - Marks, Anne; Wilson, Valerie; Crisp, Jackie
<x xml:space="preserve">Abstract</x> Aim: The aim of this study was to explore the management of type 1 diabetes in Australian primary schools: kindergarten-Year 2, from the parent's perspective. The study questions were: What diabetes treatment is being delivered? Who is providing the treatment? Where is the treatment given? Methods: A cross sectional, descriptive approach was used to collect data from parents (66) of children with type 1 diabetes attending an Australian primary school (kindergarten-Year 2). An online self-administered questionnaire was designed in Survey Monkey and was available via a dedicated Facebook page. Data were analysed using statistical analysis (SPSSv21). Results: Blood glucose testing was occurring for all children, with 49% of children self testing. 77% of children were receiving an insulin bolus or injection at school. 34% was provided by the child and 53% of insulin was given via pump. Teachers, parents and teacher's aides also provided insulin at school. There was a statistically significant association between the number of children receiving insulin at school and the insulin delivery device, χ2 = 16.75, df = 1, p ≤ 0.000). Children using insulin pump therapy were more likely (97%) to receive insulin at school than children who used injections (55%). Children who were able to self-administer insulin were more likely to receive insulin (93%) at school than children who were unable to self-administer insulin (65%) (χ2 = 7.38, df = 1, p = 0.007) 81% of children received diabetes treatment in the classroom, with the remainder in the school administration office. Conclusion: Insulin administration across Australian primary schools was inconsistent. Not all children were receiving the recommended insulin treatment. Insulin pump therapy appears to increase access to this treatment at school.